2008
DOI: 10.1002/cncr.23364
|View full text |Cite
|
Sign up to set email alerts
|

Randomized, placebo‐controlled, pilot study evaluating aprepitant single dose plus palonosetron and dexamethasone for the prevention of acute and delayed chemotherapy‐induced nausea and vomiting

Abstract: BACKGROUND. The combination of palonosetron and aprepitant is safe and effective in the prevention of chemotherapy‐induced emesis (CIE). The purpose of this pilot study was to ascertain the effectiveness of 1‐day versus 3‐day aprepitant in the prevention of acute and delayed nausea and vomiting in patients who were receiving highly emetogenic chemotherapy. METHODS. This study was institutional review board‐approved and informed consent was obtained before this study was begun. This was a pilot, single‐institut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
58
2

Year Published

2008
2008
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 77 publications
(62 citation statements)
references
References 15 publications
2
58
2
Order By: Relevance
“…Such regimens should be used with initial chemotherapy, rather than assessing the patient's emetic response with less effective treatment. The pilot study by Herrington et al 4 compared two dosing schedules of aprepitant (1 day v 3 days). No differences in rates of complete response and emetic episodes for the overall study period were reported.…”
Section: Anticipatory Nausea and Vomitingmentioning
confidence: 99%
“…Such regimens should be used with initial chemotherapy, rather than assessing the patient's emetic response with less effective treatment. The pilot study by Herrington et al 4 compared two dosing schedules of aprepitant (1 day v 3 days). No differences in rates of complete response and emetic episodes for the overall study period were reported.…”
Section: Anticipatory Nausea and Vomitingmentioning
confidence: 99%
“…Thus, the question that whether palonosetron should be the preferred 5-HT 3 RA when aprepitant is used should be addressed. To date, limited information is available about the combination of palonosetron and aprepitant [30][31][32]. The newest combination antiemetic therapy with palonosetron and aprepitant plus corticosteroid may lead to further improvement in the control of CINV.…”
Section: Discussionmentioning
confidence: 99%
“…This paradox will need further study in the setting of single day antiemetic regimens, which are highly effective in emesis control, but also seem to lose on control of nausea over several days [16].…”
Section: Usage Of Corticosteroidsmentioning
confidence: 99%